2002
DOI: 10.1128/jvi.76.15.7444-7452.2002
|View full text |Cite
|
Sign up to set email alerts
|

Intersubtype Human Immunodeficiency Virus Type 1 Superinfection following Seroconversion to Primary Infection in Two Injection Drug Users

Abstract: In this study, we describe two cases of human immunodeficiency virus type 1 (HIV-1) intersubtype superinfection with CRF01_AE and subtype B strains, which occurred in two injection drug users participating in a prospective cohort study in Bangkok, Thailand. In both cases, the superinfecting strain was detected by molecular and serologic analyses several weeks after complete seroconversion to the primary infection with a strain belonging to a different subtype. Superinfection occurred despite specific T-cell an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
122
0
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 161 publications
(130 citation statements)
references
References 44 publications
(43 reference statements)
4
122
0
3
Order By: Relevance
“…Therefore, it is likely that the susceptibility to superinfection is higher during the first year following primary infection, when HIV-1-specific humoral immunity is not fully developed, and the discrepancies between the abovementioned studies might be explained by differences in the time elapsed between the initial and the second infection. This hypothesis is supported by initial observations in HIV-2-infected macaques, which can only become productively superinfected by a distinct HIV-2 virus within 8 weeks following primary infection [22], and by a substantial percentage of documented superinfections that occurred within one year of primary HIV-1 infection in humans [11,30,31,33,34].…”
Section: Role Of Neutralizing Antibodies In Hiv-1 Superinfectionsupporting
confidence: 63%
See 4 more Smart Citations
“…Therefore, it is likely that the susceptibility to superinfection is higher during the first year following primary infection, when HIV-1-specific humoral immunity is not fully developed, and the discrepancies between the abovementioned studies might be explained by differences in the time elapsed between the initial and the second infection. This hypothesis is supported by initial observations in HIV-2-infected macaques, which can only become productively superinfected by a distinct HIV-2 virus within 8 weeks following primary infection [22], and by a substantial percentage of documented superinfections that occurred within one year of primary HIV-1 infection in humans [11,30,31,33,34].…”
Section: Role Of Neutralizing Antibodies In Hiv-1 Superinfectionsupporting
confidence: 63%
“…While the neutralizing antibody response was found to be low, a cellular response of this magnitude and breath did not translate into protection against the second HIV-1 strain even though its sequence only differed by 12%. Thus, these and additional well-documented cases demonstrated that superinfection can occur in the context of limited HIV-1-specific cytotoxic T cell responses mostly directed against a single epitope [10,35], yet it is not prevented by the presence of broad responses to multiple epitopes [9,11,34,39].…”
Section: Role Of T Cell Responses In Hiv-1 Superinfectionmentioning
confidence: 99%
See 3 more Smart Citations